ANT1 Activation and Inhibition Patterns Support the Fatty Acid Cycling Mechanism for Proton Transport - Kreiter, Jürgen; Rupprecht, Anne; Škulj, Sanja; Brkljača, Zlatko; Žuna, Kristina; Knyazev, Denis G; Bardakji, Sarah; Vazdar, Mario; Pohl, Elena E (International journal of molecular sciences, 2021)
Adenine nucleotide translocase (ANT) is a well-known mitochondrial exchanger of ATP against ADP. In contrast, few studies have shown that ANT also mediates proton transport across the inner mitochondrial membrane. The results of these studies are controversial and lead to different hypotheses about molecular transport mechanisms. We hypothesized that the H+-transport mediated by ANT and uncoupling proteins (UCP) has a similar regulation pattern and can be explained by the fatty acid cycling concept. The reconstitution of purified recombinant ANT1 in the planar lipid bilayers allowed us to measure the membrane current after the direct application of transmembrane potential ΔΨ, which would correspond to the mitochondrial states III and IV. Experimental results reveal that ANT1 does not contribute to a basal proton leak. Instead, it mediates H+ transport only in the presence of long-chain fatty acids (FA), as already known for UCPs. It depends on FA chain length and saturation, implying that FA's transport is confined to the lipid-protein interface. Purine nucleotides with the preference for ATP and ADP inhibited H+ transport. Specific inhibitors of ATP/ADP transport, carboxyatractyloside or bongkrekic acid, also decreased proton transport. The H+ turnover number was calculated based on ANT1 concentration determined by fluorescence correlation spectroscopy and is equal to 14.6 ± 2.5 s-1. Molecular dynamic simulations revealed a large positively charged area at the protein/lipid interface that might facilitate FA anion's transport across the membrane. ANT's dual function-ADP/ATP and H+ transport in the presence of FA-may be important for the regulation of mitochondrial membrane potential and thus for potential-dependent processes in mitochondria. Moreover, the expansion of proton-transport modulating drug targets to ANT1 may improve the therapy of obesity, cancer, steatosis, cardiovascular and neurodegenerative diseases.
Keywords: Mitochondria; arachidonic acid; Adenine Nucleotide Translocator 1; iontový transport; Mice; Membrane Potential, Mitochondrial; zvířata; mitochondrial transporter; protony; Protons; mastné kyseliny; Protein Conformation; Fatty Acids; konformace proteinů; membránový potenciál mitochondrií; mitochondrie; ADP/ATP carrier protein; translokátor adeninových nukleotidů 1; myši; proton transport; Animals; Ion Transport; long-chain fatty acids; fatty acid anion transport